Sagot :
Answer:
y = (x + 1)² - 31
y = x² + 2x - 30
To complete the square, the same value needs to be added to both sides
y + ? = x² + 2x + ? - 30
To complete the square x² + 2x + 1 = (x + 1)² add 1 to the expression
y + ? = x² + 2x + 1 - 30
Since 1 was added to the right side, also add 1 to the left side
y + 1 = x² + 2x + 1 - 30
Using a² + 2ab + b² = (a + b)², factor the expression
y + 1 = (x + 1)² - 30
Move constant to the right side and change its sign
y = (x + 1)² - 30 - 1
calculate the difference
y = (x + 1)² - 31
So the answer is y = (x + 1)² - 31
Step-by-step explanation:
Sana makatulong.